Inpatient health care utilization by children and adolescents with systemic lupus erythematosus and kidney involvement. Issue 3 (26th February 2013) - Tanzer, Marie; Tran, Cheryl; Messer, Kassandra L.; Kroeker, Amber; Herreshoff, Emily; Wickman, Larysa; Harkness, Courtney; Song, Peter; Gipson, Debbie S.
Abstract: Objective: To evaluate inpatient health care utilization for children with systemic lupus erythematosus (SLE) with and without kidney disease. Methods: The Healthcare Cost and Utilization Project Kids' Inpatient Database for the years 2000, 2003, and 2006 was used for this analysis. SLE hospitalizations from the 2006 cohort were identified and classified as those with versus without kidney involvement by International Classification of Diseases, Ninth Revision, Clinical Modification codes. Analyses were performed to examine determinants of hospitalization charges and changes in charges over time. Results: In the US, 7, 390 SLE‐related pediatric hospitalizations generated 267 million in total charges in 2006. Of these, 4, 193 discharges had kidney involvement. The average hospitalization charge was greater for SLE patients with kidney involvement compared to those without kidney involvement (43, 100 versus 28, 500; P < 0.0001). In multivariate analysis, kidney involvement remained a significant predictor of hospitalization charges, independent of demographic and hospital characteristics ( P < 0.0001). SLE‐associated acute kidney failure, transplant, and end‐stage kidney disease resulted in greater hospitalization charges than SLE without kidney involvement by 74, 900 ( P < 0.0001), 32, 700 ( P = 0.0002), and 27, 400 ( P < 0.0001), respectively. Conclusion: In the US, >7, 000 hospitalizations occurred in 2006 among children with SLE, with nearly 57% demonstrating kidney involvement. Kidney involvement is a major determinant of hospitalization charges for these children. This study represents one of the first large‐scale assessments of in‐hospital health care utilization by children with SLE.